We the hunted - Martin, Jesse M.; Leece, A.B.; Herries, Andy I.R.; Baker, Stephanie E.; Strait, David S. (South African Journal of Science, 2024)
Classic depictions of human evolutionary ecology cast Homo as predator and other hominins, including Paranthropus robustus, as prey. Such hypotheses rest on a small number of fossils that exhibit evidence of carnivore predation, including the iconic SK 54 cranium from Swartkrans in South Africa. Here we demonstrate that the SK 54 cranium shares its closest affinities with H. erectus sensu lato rather than P. robustus. Demonstrating that Homo was prey for leopards at Swartkrans weakens the historically significant hypothesis that Homo was better able to avoid predation because of being behaviourally and technologically advanced compared to Paranthropus. Subsequent ideas about hominin palaeobiology derived from this hypothesis warrant reconsideration. Significance: • The small sample of early Homo from southern Africa is increased by the allocation of the SK 54 cranium to that genus. • Evidence from Swartkrans suggests that Homo was prey for leopards. • Hypotheses concerning the biology, behaviour, and technological capabilities of Homo and P. robustus stemming from Brain’s seminal work, The Hunters or the Hunted?, should be reassessed.